REKONTRUKSI ḤADÎTS MAUḎHÛ’ (STUDI ḤADÎTS- ḤADÎTS ḌA‘ÎF) - Ash, Abil; Choiriyah, Alya Mardiyatul (Institut Agama Islam Ngawi, 2025)
False hadiths (ḥadîts mauḏhû’) are those deliberately fabricated by liars (al-kadzâb) and falsely attributed to the Prophet Muhammad saw. These hadiths are created without a clear foundation and often accompanied by fabricated chains of transmission (sanad). Ibn Ṣalâh and Imam Jalâluddîn al-Suyûṭî classify false hadiths into two types: (1) those deliberately fabricated without a valid chain of transmission (lâ aşla lahu), and (2) those where the error in transmission occurs unintentionally, but with a clear sanad. This research employs a hadith criticism analysis approach by tracing the chain of transmission and examining the content (matan) of the relevant hadiths. The study is based on a literature review of classical works by hadith scholars and critics. The analysis focuses on hadiths categorized as false and applies established hadith criticism principles. The research findings show that the main issues of fabricated hadiths include the absence of a clear foundation (lâ aşla lahu), the lack of a valid chain of transmission (lâ isnâda lahu), and content that contradicts the principles of Shari’ah and logical reasoning. Additionally, false hadiths often lack asbâb al-wurûd (the reasons for the revelation of the hadith), possessing only a vague historical origin. Therefore, the narration of false hadiths must be stopped and should not be spread to the public. Keywords: False Hadiths, ḥadîts mauḏhû’, Fabrication of Hadith